A model analysis on the knowledge, attitude, and readiness of ELVs policy among Malaysians: A cross-sectional study - Ismail, Rozmi; Sitinjak, Charli; Tahir, Zurinah; Che Rose, Rosniza Aznie; Mat Yazid, Muhamad Razuhanafi; Harun, Zambri; Suparjo Noordin, Nur Atiqah (Frontiers in Built Environment, 2023)
The issue of End-of-life vehicles (ELV) in Malaysia has recently deep attention from the government. To reduce the number of ELVs that have not been adequately managed, the Malaysian government has launched a variety of programs. Initiatives like offering rewards to those who want to turn up their damaged vehicles are similar to The effort to trade in their old automobiles was undertaken, however, it was unsuccessful due to a lack of cooperation from Malaysians. The purpose of this study is to examine the sociological aspects of community acceptance of ELV legislation in Malaysia. This study specifically aims to assess community knowledge, attitudes, and readiness to implement ELV management in Malaysia. 630 people participated in a cross-sectional survey that was performed across Malaysian states (Pulau Pinang, Kelantan, Johor, Melaka, Selangor, and Kuala Lumpur). A collection of questions was distributed face-to-face after passing the steps of satisfying validity and reliability tests, and then descriptive tests and multiple regression tests were run to determine correlations between variables. The study's findings revealed that people's knowledge, attitudes, and readiness toward ELV policies were significantly influenced by their length of stay, level of education, and ownership of a vehicle (overall R2 = 0.663, VIF = 1,612, p = 0.000). It was also discovered that knowledge and attitude together were able to determine community readiness in implementing ELV policies in Malaysia. The findings of this study demonstrate how important it is for the government to take into account the knowledge and attitudes of the populace before implementing the ELV policy in Malaysia.